TNF-α and Th2 cytokines induce atopic dermatitis–like features on epidermal differentiation proteins and stratum corneum lipids in human skin equivalents - Danso, MO; Van Drongelen, V; Mulder, A; Van Esch, J; Scott, H; Van Smeden, J; El Ghalbzouri, A; Bouwstra, JA (Elsevier, 2014)
Atopic dermatitis (AD) is a chronic inflammatory skin disease in which the skin barrier function is disrupted. In this inflammatory AD environment, cytokines are upregulated, but the cytokine effect on the AD skin barrier is not fully understood. We aimed to investigate the influence of Th2 (IL-4, IL-13, IL-31) and pro-inflammatory (tumor necrosis factor alpha (TNF-α)) cytokines on epidermal morphogenesis, proliferation, differentiation, and stratum corneum lipid properties. For this purpose, we used the Leiden epidermal model (LEM) in which the medium was supplemented with these cytokines. Our results show that IL-4, IL-13, IL-31, and TNF-α induce spongiosis, augment TSLP secretion by keratinocytes, and alter early and terminal differentiation-protein expression in LEMs. TNF-α alone or in combination with Th2 cytokines decreases the level of long chain free fatty acids (FFAs) and ester linked ω-hydroxy (EO) ceramides, consequently affecting the lipid organization. IL-31 increases long chain FFAs in LEMs but decreases relative abundance of EO ceramides. These findings clearly show that supplementation with TNF-α and Th2 cytokines influence epidermal morphogenesis and barrier function. As a result, these LEMs show similar characteristics as found in AD skin and can be used as an excellent tool for screening formulations and drugs for the treatment of AD.